Los contactos del español con lenguas amerindias y europeas de migración en la clase de ELE - Mário Domingues Cruz (Recherches, 2019)
Taking the demands of 21st century education into account, we believe that it is necessary to integrate linguistic diversity in our discourses and practices in the Spanish as a Foreign Language (ELE) class, reflecting on the changes that occurred in Spanish due to contacts that have existed with other languages of indigenous origin (Nahuatl, Quechua, Guarani, etc.) and European (such as Italian). This article intends to present a case study with Spanish A2/B1 students related to the subject of Spanish and the Amerindian and European contact languages.